Qualidade física do solo, armazenamento de água e erosão hídrica em sistemas de produção de grãos na região central de Minas Gerais - Silva, Lucas de Castro Moreira da (2020)
Soil physical quality is determined by several variables which have a direct influence on soil chemical and biological properties, thus constituting a central function in the agroecosystem. Considering the factors that influence plant growth and development, soil moisture is the predominant property, as it directly affects other physical attributes. The central region of the state of Minas Gerais, Brazil, inserted in the Cerrado biome, presents a poorly distributed rainfall regime, which limits agricultural activity in rainfed conditions. In addition, the occurrence of summer crops in the summer harvest is recurrent, which compromises the productivity of the crops due to the water deficit. The low availability of water due to poor rainfall distribution can be accentuated if there is soil structure degradation, compromising soil physical quality. Practices that result in increased infiltration and water storage in the soil profile to meet plant demand, as well as promoting deeper root development to allow plants access water in deeper layers, resulting in increased organic matter and reduced soil compaction are essential for successful agricultural production. The study aims evaluate soil water storage, soil structural quality, runoff and soil losses by water erosion, as well asmaize and soybean yield in different crop rotation systems after five years of implantation of no-till system. The evaluation of soil water storage was done by electrical resistivity tomography method and the soil structural quality was evaluated through the Least Limiting Water Range approach. The evaluation of water losses by runoff and soil losses by water erosion was carried out through the monitoring of runoff plots in the field. The results indicate that more diversified cropping systems, especially those involving rotation with forages with an aggressive root system, lead to improvements in soil physical condition, produce satisfactory biomass to provide adequate soil cover, promote greater water storage, reduce soil, water and nutrient losses and increase the crop yield.